Identification of taxonomic changes in the fecal bacteriome associated with colorectal polyps and cancer: potential biomarkers for early diagnosis - Grion, Beatriz Alessandra Rudi; Fonseca, Paula Luize Camargos; Kato, Rodrigo Bentes; García, Glen Jasper Yupanqui; Vaz, Aline Bruna Martins; Jiménez, Beatriz Nafría; Dambolenea, Ainhoa Lapitz; Garcia-Etxebarria, Koldo; Brenig, Bertram; Azevedo, Vasco; Bujanda, Luis; Banales, Jesus M.; et al. (Frontiers in Microbiology, 2024)
Colorectal cancer (CRC) commonly arises in individuals with premalignant colon lesions known as polyps, with both conditions being influenced by gut microbiota. Host-related factors and inherent characteristics of polyps and tumors may contribute to microbiome variability, potentially acting as confounding factors in the discovery of taxonomic biomarkers for both conditions. In this study we employed shotgun metagenomics to analyze the taxonomic diversity of bacteria present in fecal This is a provisional file, not the final typeset article samples of 90 clinical subjects (comprising 30 CRC patients, 30 with polyps and 30 controls). Our findings revealed a decrease in taxonomic richness among individuals with polyps and CRC, with significant dissimilarities observed among the study groups. We identified significant alterations in the abundance of specific taxa associated with polyps (Streptococcaceae, Lachnoclostridium, and Ralstonia) and CRC (Lactobacillales, Clostridiaceae, Desulfovibrio, SFB, Ruminococcus, and Faecalibacterium). Clostridiaceae exhibited significantly lower abundance in the early stages of CRC. Additionally, our study revealed a positive co-occurrence among underrepresented genera in CRC, while demonstrating a negative co-occurrence between Faecalibacterium and Desulfovibrio, suggesting potential antagonistic relationships. Moreover, we observed variations in taxonomic richness and/or abundance within the polyp and CRC bacteriome linked to polyp size, tumor stage, dyslipidemia, diabetes with metformin use, sex, age, and family history of CRC. These findings provide potential new biomarkers to enhance early CRC diagnosis while also demonstrating how intrinsic host factors contribute to establishing a heterogeneous microbiome in patients with CRC and polyps.